Description of respiratory syncytial virus genotypes circulating in Colombia - Viviana Avila; Eliana Calvo; Juliana Barbosa; Myriam L Velandia-Romero; Jaime E. Castellanos (Journal of Infection in Developing Countries)
Introduction: Respiratory syncytial virus (RSV) is the most common cause of acute respiratory infections in children younger than two years but also produces infection in older children and even reinfection in people of any age, a characteristic related to the existence of different infecting subtypes and genotypes. Although Colombia has established the surveillance of classical respiratory viruses, there is no information about the RSV genotypes circulating in Colombian patients.